Ultrasound in Screening for Neonatal Adrenal Hemorrhage - Felc, Zlata (American Journal of Perinatology, 1995)
Neonatal adrenal hemorrhage is common. Relatively large size and extensive vascularity of the gland results in its vulnerability to trauma and traumatic asphyxial injuries. The reported incidence from necropsies is 1.7 per 1000 births. Ultrasound scans were performed on each of 8374 consecutive newborns delivered throughout 48 months ending December 31,1993, in the Department of Obstetrics and Gynaecology. During our screening, 16 cases of adrenal hemorrhage (10 males and 6 females) were noted at an incidence of 1.9 per 1000. All of the cases of adrenal hemorrhages remained intracapsular with spontaneous resolution. Thirteen cases were right sided, two cases were left sided, and one case was bilateral. None required surgical exploration. Neonatal treatment included further phototherapy in 12 cases, blood transfusions in five cases, and antibiotics in three cases. Signs of transient adrenocortical insufficiency were observed in one child.
Keywords: Neonatal ultrasound; adrenal hemorrhage; incidence